RANCANG BANGUN SISTEM INFORMASI PERPUSTAKAAN PADA SEKOLAH SMK YADIKA 13 TAMBUN UTARA BERBASIS WEB - Dewi Pratiwi; Sari Hartini; Siti Marlina (LPPM Universitas Bina Sarana Informatika, 2018)
SMK Yadika Library 13 Tambun Utara is a Vocational High School Library which has library management personnel, has a collection of books according to the standard of Vocational High School Library, has adequate tools and equipment in the Library room. Students and students have been required to become a member of the School Library to facilitate the process of borrowing books. But the process of service is currently done conventionally that all the data collection process is still written in a book and when searching the required data must open the book and check the book one by one. This leads to slowness in the process of searching data, borrowing and return transactions, or making a report. To meet these needs, the efforts undertaken by the Library is to utilize a Library Information Systems-based technology website. It is expected to help Library staff in managing data, preparation of reports quickly and accurately. And help students in finding the required books.